The role of ionic liquids in the pharmaceutical field: an overview of relevant applications - Pedro, Sónia N. (2020)
Solubility, bioavailability, permeation, polymorphism, and stability concerns associated to solid-state pharmaceuticals demand for effective solutions. To overcome some of these drawbacks, ionic liquids (ILs) have been investigated as solvents, reagents, and anti-solvents in the synthesis and crystallization of active pharmaceutical ingredients (APIs), as solvents, co-solvents and emulsifiers in drug formulations, as pharmaceuticals (API-ILs) aiming liquid therapeutics, and in the development and/or improvement of drug-delivery-based systems. The present review focuses on the use of ILs in the pharmaceutical field, covering their multiple applications from pharmaceutical synthesis to drug delivery. The most relevant research conducted up to date is presented and discussed, together with a critical analysis of the most significant IL-based strategies in order to improve the performance of therapeutics and drug delivery systems.